Clinical-radiological characteristics and treatment of pulmonary epitheloid hemangioendotelioma, report of a case: Características clínico-radiológicas y tratamiento del hemangioendotelioma epiteloide pulmonar, reporte de un caso - Malpartida Palomino, Robert (2018)
ABSTRACT:Epitheloid Hemangioendothelioma is a rare tumor, of low prevalence, with a higher incidence in the female sex in a 3: 1 ratio. The clinical behavior is unpredictable, being the lungs and the liver the most affected organs. The clinical manifestations are diverse and present with weight loss, cough, hemoptysis, chest pain, pleural effusion and dyspnea. Typically it manifests in both lungs with the presence of multiple nodules and infiltration of the pleura that are discovered incidentally by images. Biopsy, histology and immunohistochemistry are essential for diagnosis. Different non-standardized treatments have been described in the world literature from surgical resection, systemic chemotherapy, radiotherapy and recently the use of vascular endothelial growth factors, a promising treatment option in unresectable advanced disease. We describe the case of a 46-year-old male patient who presented epithelioid pulmonary hemangioendothelioma with bilateral and pleural involvement who received systemic chemotherapy with carboplatin and pemetrexed with partial response after first-line treatment; continued with maintenance pemetrexed, to maintain stable disease, with a massive hemoptysis that is controlled with medical treatment, radiotherapy is indicated at primary lung for second line initiation. Key words: Pulmonary Epitheloid Hemangioendothelioma; Clinical features; Radiological characteristics; Treatment. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1598